Evaluation of fracturability of shale reservoirs in the longmaxi formation in southern sichuan basin - Guo, Ying; Wang, Dapeng; Han, Xiaoying; Zhang, Kaixun; Shang, Xiaofei; Zhou, Song (Frontiers in Earth Science, 2022)
Major breakthroughs have been made in the exploration and development of shale gas in the Longmaxi Formation in the southern Sichuan Basin, China. The previous have adopted various methods to study the fracturability of shale, but the quantitative characterization of the comprehensive properties of shale during hydraulic fracturing is still difficult. For this reason, in this study, taking the Longmaxi Formation shale in the Changning and Luzhou Blocks in the southern Sichuan Basin as an example, the mineral composition, petrophysical properties, rock mechanical properties and in-situ stress of the shale were systematically studied using X-ray diffraction, pulsed porosity-permeability analysis, rock mechanics and in-situ stress tests. Furthermore, the brittle mineral content, elastic modulus, and in -situ stress parameters were calculated, and the Analytic Hierarchy Process (AHP) method was adopted to establish a comprehensive evaluation index of shale fracturability. The research results show that the shale of the Longmaxi Formation in southern Sichuan is dominated by mixed shale facies, and it has the characteristics of high content of brittle minerals, low porosity, large compressive strength and Young’s modulus, and small value of in-situ stress difference coefficient. Therefore, the Longmaxi Formation shale has good fracturing conditions. TOC and quartz contents have important effects on the fracturability of the Longmaxi shale. The analytic hierarchy process was adopted to determine the weight coefficients of the modulus brittleness index, mechanical brittleness index, in-situ stress difference coefficient, rock compressive strength and TOC content. Furthermore, a comprehensive evaluation index of fracturability was constructed. Calculations show that the comprehensive fracability indices of shale in the Changning and Luzhou Blocks are 0.49 and 0.59, respectively. Moreover, the quality of shale in the Luzhou Block is better than that in the Changning Block, which is related to the organic matter and quartz content and the microscopic pore structures inside the shale.